Morphological response of the Brahmaputra-Padma-Lower Meghna river system to the Assam earthquake of 1950 - Sarker, Maminul Haque (2009)
The channels of the great rivers of Bangladesh are highly dynamic and their banklines change continuously, consuming large areas of floodplain and making thousands of people landless. As a result, bank erosion is a serious cause of poverty in Bangladesh. Severe bank retreat associated with net widening of the Jamuna, Padma and Lower Meghna Rivers during the last 50 years has greatly increased the suffering of the people. Changes in the width and planform patterns of these rivers indicate that they have not been operating in dynamic equilibrium. However, the causes of instability and planform metamorphosis remain contested. This is significant as identifying the causes of the observed channel adjustments would be of great interest not only to river scientists and engineers, but also to planners attempting better to manage the nation's natural and human resources.